Toward an integrated human adenovirus designation system that utilizes molecular and serological data and serves both clinical and fundamental virology - Aoki, Koki (2011)
The following proposals contribute toward elaborating a robust system for designating human adenovirus (HAdV) types. Our stance is that the system should be based on genomic sequence data, clinically relevant, easy to comprehend, and well integrated with the established immunotyping scheme. The main considerations are framing the criteria used to define a “type” and dealing with an increasing number of intertypic recombinants.